Biochemical Characterization of Arylamine N-acetyltransferases From Vibrio vulnificus - Liu, Xinning; Liu, Yuanchang; Zhao, Guangjian; Zhang, Yidan; Liu, Lu; Wang, Juan; Wang, Yifan; Zhang, Siyu; Li, Xin; Guo, Dongliang; Wang, Peng; Xu, Ximing (Frontiers in Microbiology, 2021)
Vibrio vulnificus is a zoonotic bacterium that is capable of causing highly lethal disease in humans; this pathogen is responsible for 95% of all seafood-related deaths in the United States. Arylamine N-acetyltransferases (NAT, E.C. 2.3.1.5) is a major family of xenobiotic-metabolizing enzymes that can biotransform aromatic amine chemicals. In this research, to evaluate the effect of NAT on acetyl group transformation in arylamine antibiotics, we first used sequence alignment to study the structure of V. vulnificus NAT [(VIBVN)NAT]. The nat gene encodes a protein of 260 amino acids, which has an approximate molecular mass of 30 kDa. Then we purified recombinant (VIBVN)NAT and determined the enzyme activity by PNPA and DTNB methods. The DTNB method indicates that this prokaryotic NAT has a particular substrate specificity towards aromatic substrates. However, (VIBVN)NAT lost most of its activity after treatment with high concentrations of urea and H2O2. In addition, we also explored the stability of the enzyme at different temperature and pH values. In analyzing the influence of metal ions, the enzyme activity was significantly inhibited by Zn2+ and Cu2+. The kinetic parameters Km and Vmax were determined using hydralazine, isoniazid, 4-amino salicylic acid, and 4-chloro-3-methylaniline as substrates, and the Tm, Tagg and size distribution of (VIBVN)NAT were observed. In particular, a molecular docking study on the structure of (VIBVN)NAT was conducted to understand its biochemical traits. These results showed that (VIBVN)NAT could acetylate various aromatic amine substrates and contribute to arylamine antibiotic resistance in V. vulnificus.